Circumference as an alternative for diameter measurement in endovascular aneurysm repair. Issue 2 (August 2015) - Tielliu, Ignace F.J.; Buijs, Ruben V.C.; Greuter, Marcel J.W.; Vainas, Tryfon; Wallis de Vries, Bas M.; Prins, Ted R.; Zeebregts, Clark J.
Abstract Appropriate sizing of endografts for endovascular aneurysm repair has traditionally been performed by one standardized method. By measuring the average of the minor and major axes in the sealing zone, the endograft size is traditionally calculated. However, no adequate scientific evaluation has been performed to validate this method. The guidelines that were published are based on theories and experience, more than scientific evidence. In case the central lumen line artery cross-section is a circular disk, the vessel diameter is a reliable estimation. Yet the aortic neck cross-section may not always be geometrically a perfect circular disk. Application of the standardized method might therefore lead to inaccurate endograft sizing, potentially leading to endoleaks. We hypothesize that in these cases the circumference of the vessel is a mathematically correct reference to deduct the appropriate endograft diameter. The following formula was applied in this study: diameter of the corresponding circle (d) equals circumference (C) divided by π<alternatives><inline-graphic xlink:href="ark:/27927/pgj22h87gkv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />d=Cπ</alternatives>. This study provides a theoretical analysis of the mathematical implications of this method. Only in case of highly irregularly shaped cylinders, the circumference-based method was more accurate than the standardized method. Nonetheless, the circumferential method was a practical reference in case the aortic neck was irregularly shaped. Also, the circumference method was accurate in all cases in deducting the diameter of a matching circle. Therefore, the hypothesis that was raised in this study has a strong theoretical base. We predict that in case this hypothesis holds true in the clinical practice, application of the circumference method might lead to less endoleaks than the standardized method.